Characteristics, Properties and Analytical Methods of Cefadroxil: A Review - Marco, Bianca Aparecida de [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2017)
Infections are the second leading cause of mortality worldwide and there are many reasons justifying the need for further studies of antimicrobial agents. Cefadroxil is a drug that has bactericidal activity and broad spectrum of action. Quantitative analyzes about cefadroxil are essential for the understanding of bioavailability, bioequivalence, and therapeutic control, which will ensure the product's characteristics and patients' safety. Thus, this study highlights a brief literature review about the drug and the existing methods developed for the determination of cefadroxil found in official and scientific papers. According to the methods found in literature, liquid chromatography and spectrophotometry of absorption in the ultraviolet region prevailed over the others. Importantly, most of the solvents used for the development of the described analytical methods are toxic to the environment, making it necessary to educate researchers and pharmaceutical companies to use nontoxic solvents to provide environmental-friendly methods and better benefits to equipments and mainly to analysts.
Keywords: Absorption spectrophotometry in the ultraviolet region; cefadroxil; high-performance liquid chromatography